Ant colony optimization with self-adaptive evaporation rate in dynamic environments - Mavrovouniotis, Michalis; Yang, Shengxiang (My University, 2014)
The performance of ant colony optimization (ACO) algorithms in tackling optimization problems strongly depends on different parameters. One of the most important parameters in ACO algorithms when addressing dynamic optimization problems (DOPs) is the pheromone evaporation rate. The role of pheromone evaporation in DOPs is to improve the adaptation capabilities of the algorithm. When a dynamic change occurs, the pheromone trails of the previous environment will not match the new environment especially if the changing environments are not similar. Therefore, pheromone evaporation helps to eliminate pheromone trails that may misguide ants without destroying any knowledge gained from previous environments. In this paper, a self-adaptive evaporation mechanism is proposed in which ants are responsible to select an appropriate evaporation rate while tracking the moving optimum in DOPs. Experimental results show the efficiency of the proposed self-adaptive evaporation mechanism on improving the performance of ACO algorithms for DOPs.
Keywords: Artificial intelligence; Dynamics; Evaporation; Parameter estimation; Ant Colony Optimization algorithms; Changing environment; Dynamic changes; Dynamic environments; Dynamic optimization problem (DOP); Evaporation rate; Optimization problems; Pheromone trails; Ant colony optimization